PENGARUH WAKTU EKSTRAKSI ULTRASONIK DAUN SIRIH HIJAU (Piper betle L) TERHADAP RENDEMEN dan SIFAT MIKROBA SEBAGAI ZAT TAMBAH GEL ANTISEPTIK: The Effect Of Ultrasonic Extraction Of Betel Leaves (Piper Betle L) On The Rendement And Properties Of Microbials As Additional Substances Of Antiseptic Gels - Fatma Sari; Ummul Habibah Hasyim; Gema Fitriyano; Rezi Salsabila Ramadhani (Universitas Darussalam Gontor, 2022)
Betel leaf (Piper betle L) is a plant that is commonly found in Indonesia. It is known that green betel leaf contains ingredients that act as antiseptics consisting of cavibetol, sesquiterpenes, hydroxy kavikol, carvakrol, estagiol, terpenes, phenylpropane, tannins and eugenol methyleugenol. Essential oils which contain phenol which is one of the antibacterial substances. The purpose of this study was to determine the effect of betel leaf extract on pH and microbial properties of antiseptic gel. The initial stages of this research are the extraction process of betel leaf with 70% ethanol solvent with time variations of 5 minutes, 10 minutes, 15 minutes, 20 minutes, and 25 minutes. Furthermore, each time variation is calculated yield results. The best yield was added to the antiseptic gel then analyzed for pH and tested for its inhibitory power as an antiseptic against Staphylococcus Aureus. Based on the research results, the yield of betel leaf extract with time variables of 5, 10, 15, 20, 25 minutes in a row are: 83.47%; 83.99%; 86.48%; 86.76%; 87.34%. In pH testing the results obtained pH 5.5. In the inhibition test, the results obtained successively, namely 18.23: 19.70: 18.82: 19.98 mm.